Conflict resolution of Indonesia-Malaysia relations and paradox of Westphalian Settlement - Suyatno, ,; Abdul Mutalib, Rozita (2013)
Indonesia-Malaysia relations have fluctuations conflict in globalized world. This is due to the increasing complexity of the problems faced by the two countries, both from the aspect of political, economic, social, and also cultural. Actors of globalization today are not only dominated by the nation-state but also by non-nation-state actors. Westphalian Settlement which at first appears as a form of conflicts between states, including the analyze conflict in Indonesia-Malaysia relations. If the force analysis using the Westphalian Settlement conflict resolution will be serious obstacles, because the two countries considered as emerging decades ago, such as Indonesia emerged in 1945 and Malaysia in 1957.At mean while globalism life of the two countries has been going on for hundreds of years, even as the Nusantara known as the home shared at that time.This paper would like to explain how conflict resolution using the Westphalian Settlement analysis contains many flaws.Therefore we need an alternative analysis that looked at the relationship between the two countries far beyond Westphalian Settlement analysis. Not only as a consequence of globalization but also realize that the roots of his history of relations between the two countries is very long age, much older than the Westphalian Treaty proclaimed.